Comparative role of complement in pneumococcal and staphylococcal pneumonia. - Coonrod, J D (1982)
To evaluate the role of complement in pneumococcal and staphylococcal pneumonia, we decomplemented rats with cobra venom factor and inoculated them intratracheally with Staphylococcus aureus or type 25 pneumococci. S. aureus produced a patchy bronchopneumonia in normal Sprague-Dawley or Lewis rats, and decomplementation did not increase the severity of staphylococcal infection in either rat strain as judged by quantitative cultures of the lungs and blood at 6, 24, and 48 h after inoculation. In contrast, decomplementation markedly increased the severity of pneumonia caused by type 25 pneumococci in Sprague-Dawley and Lewis rats. In Sprague-Dawley rats, decomplementation significantly increased the number of bacteria in the lungs at 3, 6, and 24 h of infection. Bacteremia developed early in decomplemented Sprague-Dawley rats, but the higher pulmonary bacterial counts did not appear to be caused by bacteremic seeding of the lungs. Decomplemented Sprague-Dawley rats inoculated intravenously with pneumococci failed to develop the very high levels of bacteria in the lungs that were observed when the rats were inoculated intratracheally. Moreover, decomplemented Lewis rats inoculated intratracheally with pneumococci developed significantly increased numbers of pneumococci in the lungs early in infection (3 and 6 h) when they had no detectable bacteremia. These data indicate that in murine models complement plays a major protective role against type 25 pneumococci in the lung, whereas complement is not important to host defense in staphylococcal pneumonia.